2004
DOI: 10.1103/physrevb.70.104404
|View full text |Cite
|
Sign up to set email alerts
|

β-detected nuclear quadrupole resonance with a low-energy beam ofLi+8

Abstract: A nuclear quadrupole resonance (NQR) spectrum of 8 Li has been observed in a single crystal of SrTiO 3 using a beam of low-energy highly polarized radioactive 8 Li + . The resonances were detected by monitoring the ␤-decay anisotropy as a function of a small audio frequency magnetic field. These results demonstrate that low energy nuclear spin polarized 8 Li can be used as a sensitive probe of the local magnetic and electronic environment in nanostructures and ultrathin films in zero static applied magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 17 publications
1
68
0
Order By: Relevance
“…Therefore, the implanted 8 Li + can monitor the depth dependence of the local magnetic field distribution in materials at nm scale by measuring the NMR lineshape in a manner analogous to conventional NMR. 2,28,29 In this work, the 8 Li + ions are decelerated to stop in the Ag overlayer deposited on each of the three YBCO samples. Implantation profiles of 8 Li + were calculated using the TRIM.SP code, 45 examples of which are shown in Fig.…”
Section: 28mentioning
confidence: 99%
“…Therefore, the implanted 8 Li + can monitor the depth dependence of the local magnetic field distribution in materials at nm scale by measuring the NMR lineshape in a manner analogous to conventional NMR. 2,28,29 In this work, the 8 Li + ions are decelerated to stop in the Ag overlayer deposited on each of the three YBCO samples. Implantation profiles of 8 Li + were calculated using the TRIM.SP code, 45 examples of which are shown in Fig.…”
Section: 28mentioning
confidence: 99%
“…It has been shown that with the formation of the metastable magnetic centers, the material becomes less absorbing in the wavelength region relevant to the photomagnetism [32], thus it is possible that the photomagnetic state would eventually grow out from the illuminated surfaces, but such an effect was apparently not sufficient to influence the magnetism on the ∼ 100 µm surface muon stopping range. A more favorable situation to study these effects is in a thin film geometry [33] using low energy muons [34] or β-NMR probes [35,36,37].…”
Section: F Sample Illuminationmentioning
confidence: 99%
“…We have established earlier that the 8 Li occupies the face centered cite in SrTiO 3 [2,11], and therefore experiences a nonvanishing EFG. Indeed a large and sharp NQR resonance was observed at 3ν q = 228.81(2) kHz with width 1.7 kHz corresponding to the | ± 2 ↔ | ± 1 transitions (see Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Recently, we have constructed two spectrometers for beta-detected nuclear magnetic resonance [1] (β-NMR) and nuclear quadrupole resonance [2] (β-NQR), using a low energy highly polarized 8 Li + beam. We report here on the first results obtained from the β-NQR spectrometer at zero applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation